(untitled) (Research, Society and Development, 2020)
The aim of the study was to analyze the profile of physical education teachers who work with the boccia. The 69 teachers’ information was obtained through a Google Forms questionnaire and contained ten closed questions. The participation of individuals in the study was voluntary, non-profit and after explaining the objectives and procedures of the research, when they agreed to participate, they answered the questionnaire. The results revealed that 60.9% of the teachers are male, 36.3% are over 40 years old, 52.2% have more than ten years of training, 42% have an undergraduate degree, 42% has between 01 and 05 years of experience with the sport, 33.4% has training frequency of up to three hours a week with athletes, 40.6% perform voluntary work, 62.3% have little command over the sports classification processes , 60.9% have a good command of the rules of the sport and 50.8% do not carry out evaluations with their athletes. Thus, there is a need to invest in the continuing education of these teachers, it seems to draw a profile of better trained technicians across all regions of the country. This process also involves a greater process of professionalization of technicians with greater knowledge about sports classification, rules and evaluation, in addition to a greater amount of hour / training based on scientific knowledge.